The impact of Fc-γ receptor polymorphisms in elderly patients with diffuse large B-cell lymphoma treated with CHOP with or without rituximab - Ahlgrimm, Manfred; Pfreundschuh, Michael; Kreuz, Markus; Regitz, Evi; Preuss, Klaus-Dieter; Bittenbring, Joerg (Blood, 2011)
Fcγ receptor (FcγR) polymorphisms have been shown to affect rituximab-mediated antibody-dependent cellular cytotoxicity. Of 512 patients with diffuse large B-cell lymphoma treated in the RICOVER-60 trial, carriers of FcγRIII 158 valine homozygous receptors (V/V) presented with a slightly decreased incidence of B-symptoms (158 V/V: 26%, V/F: 35%, phenylalanine receptors [F/F]: 42%; P = .037). Survival curves of all FcγR single nucleotide polymorphisms were superimposable after cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP); but after CHOP with rituximab (R-CHOP), event-free survival (EFS) and progression-free survival (PFS), but not overall survival, of FcγRIIIa 158 F/F had a trend to be lower than those of 158 V/F and 158 V/V: 3-year EFS: FcγRIIIa 158 F/F: 64.5%, 158 V/F: 70.2%, 158 V/V: 76.9% (log-rank test: P = .224 F/F vs V/V; P = .285 F/F vs V/F + V/V); 3-year PFS: FcγRIIIa 158 F/F: 68.3%, V/F: 76.1%, V/V: 80.5% (log-rank test: P = .233 for F/F vs V/V; P = .185 for F/F vs V/F + V/V). By multivariate analysis adjusting for International Prognostic Index factors, relative risk of F/F compared with V/F plus V/V was 1.80 (P = .052) for PFS and 1.55 (P = .120) for EFS. The interaction of R-CHOP, but not CHOP with FcγRIIIa polymorphisms, indicates a window of opportunity for CD20 antibodies designed to mediate enhanced antibody-dependent cellular cytotoxicity.